Menumbuhkan Jiwa Kepemimpinan Sejak Dini: Pelatihan Dasar Kepemimpinan bagi Siswa SMA Negeri 10 Kabupaten Pangkep - Abdul Majid; Naufal Qadri Syarif; Hasruddin Nur; Abdurrahman Achmad; Iyan Iyan (Yayasan Literasi Sains Indonesia, 2026)
Fostering leadership spirit from an early age is a strategic effort to develop young generations who are responsible, confident, and capable of contributing positively to their school and community. This Community Service activity aimed to enhance students’ basic leadership knowledge and skills through a Basic Leadership Training program conducted in November 2025 at SMA Negeri 10 Kabupaten Pangkep. The implementation method consisted of preparation and coordination with the school, needs analysis, training sessions delivered through interactive lectures, group discussions, leadership simulations, reflective activities, and evaluation using questionnaires and participatory observation. The participants were students involved in school organizations and class representatives. The results indicated an improvement in students’ understanding of leadership concepts, effective communication, organizational management, teamwork, and responsible decision-making. In addition, students demonstrated increased self-confidence and collaboration skills during practical sessions and simulations. Participant evaluations showed positive responses toward the contextual and applicable training materials and methods. In conclusion, the Basic Leadership Training conducted in November 2025 at SMA Negeri 10 Kabupaten Pangkep was effective in fostering students’ leadership spirit from an early stage and is recommended to be implemented continuously as part of character development and student organization strengthening programs at school